Explorations and encounters in French - Fornasiero, F. J.; Mrowa-Hopkins, Colette (The University of Adelaide Press, 2010)
The essays selected for inclusion in 'Explorations and Encounters in French' bring together many of the current research strands in French Studies today, tapping into current pedagogical trends, analyzing contemporary events in France, examining the Franco-Australian past, while reviewing teaching practice and the culture of teaching
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Geschichte 1900-2000; Alltag, Brauchtum; Französisch; Geschichte; French language / Study and teaching / Congresses; French language / Study and teaching / Australia / Congresses; Interkulturalität; Französischunterricht; Australien; Frankreich; Pazifischer Raum; Pacific Area / Discovery and exploration / French / Congresses; France / Relations / Australia / History / Congresses; Australia / Relations / France / History / Congresses; France / Civilization / 20th century / Congresses; France / Civilization / 21st century / Congresses; France / Social life and customs / 20th century / Congresses; France / Social life and customs / 21st century / Congresses; Konferenzschrift